KERAGAAN KOMODITAS LADA INDONESIA (Studi Kasus di Kabupaten Bangka) - ROOSGANDHA ELIZABETH (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
It has been admitted that plantation sub-sector as an important one comparedwith the others in agricultural sector. Pepper is one of the plantation commodities thattraditionally contributes to the Indonesia’s foreign exchange. This commodity is alsothe oldest and native species of Indonesian spices, which has been marketed in theworld wide. But, in the current situation, which is the still adversely affected by globaleconomic crises, the pepper export has been decreased, even how days, the pepperproduction is lower then Vietnams. This decreased production of pepper, especiallyfor example in Bangka district, is caused by inefficiently traditional management, withhigh cost, lack of labors, and uncertainly of pepper price, which is still controlled bymiddle-man. In order to improve the sub-sector plantation, especially the pepperplantation, it is needed to revitalize the extension program and further provide thecredit scheme for farmers.